Accountable Care Organization Implementation Experiences and Rural Participation: Considerations for Nurses. (January 2017) - Bagwell, Matt Thomas; Bushy, Angeline; Ortiz, Judith
Abstract : BACKGROUND: Little is known about how accountable care organizations (ACOs) participate with rural health providers. This pilot study examines ACO participation with rural health clinics (RHCs). METHODS: Telephone interviews with 8 ACO administrators were conducted to determine the early implementation experiences of these organizations, and their participation with rural health providers, such as RHCs, using qualitative content analysis, ACO characteristics, and emerging themes from the ACO executive responses was identified. RESULTS: Three predominant themes emerged: 1) ACOs are growing in size and number and have various organizational structures; 2) there is an expanding emphasis on preventive primary care and chronic disease management for patients; and 3) there is a need for improved information technology integration with clinical services and financial systems. CONCLUSION: Of 8 participants, 7 reported that their ACO was planning to expand into rural areas and partner with rural providers.